Relative values of maximal isometric strength in lower limbs across different sports disciplines in high-performance athletes - Martín-Miguel, I.; Torrontegi-Ronco, E.; Martínez-Ortega, J. D.; Moreno-Martín, A.; Montalvo-Zenarruzabeitia, Z. (The Journal of Strength and Conditioning Research, 2025)
This study aimed to establish reference values for relative strength in lower limb dynamometry among high-performance athletes across various sports disciplines and to compare the differences in relative strength between these disciplines. In total, 297 elite athletes (female athletes:155; male athletes:142) from 26 different sports participated, grouped into categories such as team sports, gymnastics, combat sports, racket sports, endurance, power track and field, weightlifting, and other. Relative strength was measured using a dynamometer through maximal isometric contractions. Knee extension and ankle plantar flexion were the tests with the highest strength application in both sexes, while external hip rotation and hip abduction showed the least force application. Analysis of variance revealed differences based on the test and sports discipline (p < 0.05). Female athletes showed differences in hip abduction, hip extension, hip flexion, knee extension, knee flexion, and ankle plantar flexion, with gymnastic sports demonstrating greater strength, particularly compared with team sports and endurance. In male athletes (p < 0.05), endurance sports showed lower strength in external hip rotation compared with racket sports, and in hip abduction compared with combat sports. The agonist-antagonist ratio indicated greater strength in internal hip rotation, hip flexion, knee extension, and ankle plantar flexion in both sexes, and hip abduction in female athletes and hip adduction in male athletes, compared with their antagonists. Significant differences were found in the hip adduction-abduction and ankle plantar-dorsal flexion ratio in gymnastics compared with the rest of sports. These findings can be used to assess athletes' physical condition, prevent injuries, and facilitate rehabilitation to optimize performance.